Menghasilkan Keunggulan Berkelanjutan Melalui Manejemen Budaya Kerja “Aswaja” di Lembaga Pendidikan - Ahmad Halid (An Nahdhoh Jurnal Kajian Islam Aswaja, 2021)
ASWAJA's work culture produces work success through building people (personality) fundamentally, namely changing the mindset about workforce and working relationship attitudes well. These two things mean achieving work success by cooperating with others accompanied by faith and good deeds, not by functioning or trying to limit the scope of their activities, close supervision and their approach. The formulation of the problem is how does the work culture of ASWAJA produce sustainable competitive advantages in educational organizations? The main purpose of this article is to demonstrate the efficacy of the